Pure pursuit method use to control unmanned motor grader - R. Yu. Sukharev (Вестник СибАДИ)
The clarification to the article published in volume 19 No. 2 (84) 2022 pp. 156-169 is the following: the article has been amended at the end, the translator of the article is indicated: the translation was made by I. N. Churilova.